Pertussis in infants under one year old: Risk markers and vaccination status—A case-control study. Issue 17 (21st April 2015) - Zamir, Chen Stein; Dahan, Dana Bardugo; Shoob, Hanna
Highlights: Low birthweight and high birth order were found to be independent risk markers for pertussis in young infants. A third of reported pertussis cases in infants occurred under age 2 months (currently recommended for the 1st pertussis vaccine dose). Reported pertussis cases over age 2 months were more likely to be unvaccinated and to have delayed vaccinations. In 2-4-month-old infants, 1 dose of pertussis vaccine gave significant protection against pertussis overall and pertussis hospitalization. The pertussis vaccine effectiveness increased with the number of vaccine doses. Abstract: Background: Pertussis is a contagious bacterial disease causing substantial health burden. Pertussis-related morbidity and mortality are highest in young infants. We investigated risk markers for pertussis and vaccination status in infants. Methods: Reported pertussis cases under one year old during 1998–2011 in the Jerusalem district were matched to controls by birthdate and residence. Data sources included epidemiological investigations, health records and vaccination records (number and dates of DTP\DTaP doses scheduled at 2, 4, 6 months). Vaccine effectiveness was calculated by number of vaccine doses stratified by age group. Timeliness of vaccine doses was also evaluated. Results: The study population included 1268 infants under 1 year: 317 pertussis cases and 951 age-matched controls (mean age 3.95 ± 3, median 2.9 months). Low birthweight (<2500 g, 12.3% in cases vs. 6.3% in controls) and high birth order (4th and above) were found to be independent risk markers. Male gender and low socio-economic status were more frequent among cases. Some 40% of the cases (127/317) were hospitalized, most of them (111/127, 87.4%) were under 4 months (mean age 2.42 ± 2.05, median 1.8 months). The distribution of the number of pertussis vaccine doses 0, 1, 2 and 3 differed considerably being 42.2%, 32.7%, 15.6%, 9.5% vs. 13.7%, 41.9%, 22.9%, 21.5% among cases and controls (≥2 m), respectively. The overall vaccine effectiveness found was 72.9%, 76.1% and 84.4%, for the 1st, 2nd and 3rd doses of a pertussis vaccine. The infant's age at the first dose of pertussis vaccine was recorded with follow-up until age 18 months. Delay was more common among cases with a lower proportion vaccinated—78.9% at 18 months vs. 99% in controls. Conclusions: Specific risk markers for pertussis in young infants were identified. Reported pertussis cases over age 2 months were significantly more likely to be unvaccinated and have delayed vaccinations. The vaccine effectiveness increased with the number of vaccine doses.